2011
DOI: 10.1073/pnas.1120270109
|View full text |Cite
|
Sign up to set email alerts
|

Preceramic maize from Paredones and Huaca Prieta, Peru

Abstract: Maize (Zea mays ssp. mays) is among the world's most important and ancient domesticated crops. Although the chronology of its domestication and initial dispersals out of Mexico into Central and South America has become more clear due to molecular and multiproxy archaeobotanical research, important problems remain. Among them is the paucity of information on maize's early morphological evolution and racial diversification brought about in part by the poor preservation of macrofossils dating to the pre-5000 cali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
111
2
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(132 citation statements)
references
References 17 publications
10
111
2
9
Order By: Relevance
“…Pairwise F ST among populations reveals low overall differentiation (Table 1), and the higher F ST values observed in South America are consistent with the decreased admixture seen in STRUCTURE. Archaeological evidence supports a more recent colonization of the highlands in South America (Perry et al 2006;Piperno 2006;Grobman et al 2012), suggesting that the observed differentiation may be the result of a stronger bottleneck during colonization of the South American highlands. …”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Pairwise F ST among populations reveals low overall differentiation (Table 1), and the higher F ST values observed in South America are consistent with the decreased admixture seen in STRUCTURE. Archaeological evidence supports a more recent colonization of the highlands in South America (Perry et al 2006;Piperno 2006;Grobman et al 2012), suggesting that the observed differentiation may be the result of a stronger bottleneck during colonization of the South American highlands. …”
mentioning
confidence: 92%
“…N A was set to 150,000, using estimates of the composite parameter 4N A m $ 0:018 from parviglumis (Eyre-Walker et al Grobman et al 2012) and estimated the remaining four parameters (a, b 1 ; b 2 ; and g).…”
Section: Convergent Highland Adaptation In Maize 1299mentioning
confidence: 99%
“…Accordingly, beginning in the 1960s, Andeanists Towle (8) and Ugent et al (9,10) sought to further their insights through microbotanical analysis of starch morphology from macrogeophytes. Their pioneering work foreshadowed the mounting role of microbotanical studies around the world, including the study area (11)(12)(13)(14)(15)(16)(17)(18). Following suit, this study contributes direct microbotanical evidence for potato within its botanical hearth at the onset of food production.…”
mentioning
confidence: 99%
“…Más hacia el sur, la ruta pudo haber sido por la costa sur de Ecuador y el norte de Perú (Dillehay, Rossen, Maggard, Stackelbeck, & Netherly, 2003;Stothert, et al, 2003;Pearsall, Chandler-Ezell, K. & Chandler-Ezell, A. 2004;Grobman et al, 2012). La difusión hacia Brasil se ha planteado a través de dos rutas: una por el sur, cruzando Los Andes hacia el suroeste de Brasil y noroeste de Bolivia y otra por el norte, siguiendo el río Orinoco y el río Amazonas (Freitas, Bendel, Allaby, & Brown, 2003) (Figura 1).…”
unclassified
“…Los registros arqueo-botánicos de granos de almidón y fitolitos de maíz asociados a las piedras moledoras, sugieren esta ruta e indican el arribo del maíz a Panamá tan temprano como hace 7,400 años AP, a la costa norte de Suramérica entre 7,900-7,670 AP., al valle medio del río Cauca en Colombia entre 7,000-6,500 AP., y a la costa sur de Ecuador y norte del Perú entre 6,700-6,500 AP (Dickau, Ranere & Cooke, 2007;Zarrillo, et al, 2008;Grobman et al, 2012;Aceituno & Loaiza, 2014) …”
unclassified